Kepemimpinan Perempuan dalam Politik Islam: Analisis Historis, Teologis, dan Sosio-Politik - Wardani, Mufti (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research examines the complex dynamics of women's leadership in Islamic politics, focusing on the interpretation of religious texts, historical developments, and contemporary realities in Muslim countries. The main objective of the research is to analyze the challenges and opportunities for women's political participation in the Islamic context, as well as identify strategies to bridge the gender gap in political leadership.The research methodology incorporates a comprehensive literature analysis, covering Islamic primary sources, works of classical and contemporary Muslim scholars, as well as case studies from various Muslim countries. An interdisciplinary approach is applied, combining theological, historical, and socio-political perspectives to provide a holistic understanding of the topic.The results show the complexity of interpretations of Islamic texts related to women's leadership, with a wide spectrum of views from conservative to progressive. The study reveals significant variations in the practice and acceptance of women's leadership in different Muslim countries, influenced by socio-political, cultural and economic factors. The research also found that increased representation of women in politics has a positive impact on gender and social issues. The research conclusions emphasize the importance of reinterpreting religious texts with a contemporary perspective, legal reforms that support women's political participation, as well as education and empowerment efforts. The research contributes to a more nuanced understanding of the intersections between Islam, gender, and politics, and offers practical recommendations for enhancing women's leadership in the context of Islamic politics. Keywords: Leadership, Women, Political Islam, Historical Abstrak Penelitian ini mengkaji dinamika kompleks kepemimpinan perempuan dalam politik Islam, dengan fokus pada interpretasi teks-teks agama, perkembangan historis, dan realitas kontemporer di negara-negara Muslim. Tujuan utama penelitian adalah untuk menganalisis tantangan dan peluang bagi partisipasi politik perempuan dalam konteks Islam, serta mengidentifikasi strategi untuk menjembatani kesenjangan gender dalam kepemimpinan politik.Metodologi penelitian menggabungkan analisis literatur yang komprehensif, meliputi sumber-sumber primer Islam, karya-karya sarjana Muslim klasik dan kontemporer, serta studi kasus dari berbagai negara Muslim. Pendekatan interdisipliner diterapkan, menggabungkan perspektif teologis, historis, dan sosio-politik untuk memberikan pemahaman holistik tentang topik ini. Hasil penelitian menunjukkan kompleksitas interpretasi teks-teks Islam terkait kepemimpinan perempuan, dengan spektrum pandangan yang luas dari konservatif hingga progresif. Studi ini mengungkapkan variasi signifikan dalam praktik dan penerimaan kepemimpinan perempuan di berbagai negara Muslim, yang dipengaruhi oleh faktor-faktor sosio-politik, budaya, dan ekonomi. Penelitian juga menemukan bahwa peningkatan representasi perempuan dalam politik memiliki dampak positif terhadap isu-isu gender dan sosial.Kesimpulan penelitian menekankan pentingnya reinterpretasi teks-teks agama dengan perspektif kontemporer, reformasi hukum yang mendukung partisipasi politik perempuan, serta upaya pendidikan dan pemberdayaan. Penelitian ini memberikan kontribusi pada pemahaman yang lebih nuansa tentang interseksi antara Islam, gender, dan politik, serta menawarkan rekomendasi praktis untuk meningkatkan kepemimpinan perempuan dalam konteks politik Islam. Kata Kunci: Kepemimpinan, Perempuan, Politik Islam, Historis